Ensuring Excellence and Quality Accreditation in Medico Legal Practices (Journal of Forensic Medicine & Toxicology, 2026)
The medico-legal system forms a critical interface between medicine and law, pivotal for the administration of justice. Its  integrity, however, is frequently compromised by the absence of standardized protocols and a formal accreditation frame work. The integration of robust quality accreditation systems, drawing parallels from established healthcare standards like  the National Accreditation Board for Hospitals & Healthcare Providers (NABH) and the National Accreditation Board  for Testing and Calibration Laboratories (NABL), is essential to address this deficiency. These standards can also be  applicable to certain aspects in the field of forensic – State Forensic Labs and Forensic Histopathology labs. Maintaining  healthcare standards and following protocols also reduces the medicolegal burden of hospitals. A structured quality  management system is imperative for ensuring precision, accountability, and integrity in all medico-legal procedures.  This is particularly crucial for post-mortem examinations, where the implementation of Standard Operating Procedures  (SOPs) for autopsy performance, dead body management, chain of custody for sample preservation, and compliant biomedical waste management prevents evidentiary contamination and procedural lapses. Also following a standard report ing format can make sure the quality of reporting is not compromised. Adopting a formal accreditation process would  minimize errors, enhance the scientific validity of forensic findings, and ensure uniformity across different centres. A  quality-accredited medico-legal framework is fundamental to upholding the principles of justice, ensuring defensibility  in court, and strengthening public confidence in both the medical and legal systems.
Keywords: Medico-legal; Quality; Accreditation; Autopsy; Standardization; Certification.